PENGARUH TEKNIK SHAPING TERHADAP KEMAMPUAN MENULIS ANAK USIA 5-6 TAHUN DI PAUD MANDA KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Khodijah, Siti; Chairilsyah, Daviq; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research is to know the effect of shaping technique on writing ability children’s age 5-6 years. The research is conducted in PAUD Manda Kecamatan Tanah Putih Kabupaten Rokan Hilir from April to Mei 2017. This is pretest and posttest group design an experimental research with 30 children as samples. Type of instrument used in this study is the observation using a sheet to record about activities that occurred during a given treatment. Based on the hypothesis test results obtained are the shaping technique is influence on writing ability children ages 5-6 years in PAUD Manda Kecamatan Tanah Putih Kabupaten Rokan Hilir. Retrieved tcount at 8,613 with sig 0000, because sig <0.05 then we can conclude that there are influence on writing abilities is significant between class with shaping technique and without shaping technique. Hypothesis testing can be seen at tcount= 8,613> t table = 2,048 it has been suggested that there is a significant influence in results between the control class and experiment class. The shaping technique had a significant effect towards children’s age 5-6 years old writing ability, at 63,69%. This is known from the different results writing ability on control class and expriment class with given shaping technique treatment.Keywords: Writing Ability, Shaping Technique